A comparison of surgical outcomes between robot and laparoscopy-assisted adenomyomectomy - Shim, Jung In (Medicine (Baltimore), 2019)
We aimed to investigate the feasibility of robotic adenomyomectomy and compared surgical outcomes between laparoscopic and robotic approaches for adenomyomectomy. We retrospectively reviewed the data of women who were diagnosed with adenomyosis and underwent adenomyomectomy through a minimally invasive approach between January 2014 and March 2018 at the CHA Gangnam Medical Center, Seoul, Republic of Korea. Patient demographics and operation-related outcomes were compared between the robotic and laparoscopic surgery groups. We evaluated 43 women who underwent adenomyomectomy through a minimally invasive approach (21 underwent a laparoscopic and 22 underwent a robotic adenomyomectomy). All 22 women who had originally been scheduled to undergo robotic adenomyomectomy could successfully undergo the robotic surgery without requiring conversion to laparotomy and/or serious complications. No statistically significant differences in patient demographics were observed between the robotic and the laparoscopic surgery groups. No significant intergroup difference was observed in the operative time, estimated blood loss, weight of the resected nodule, and length of hospitalization (160.0 vs 212.5 min, P = .106; 500.0 vs 300.0 mL, P = .309; 60.0 vs 70.0 g, P = .932; and 5.0 vs 6.0 days, P = .277). No serious perioperative complications were observed in either group. Robotic adenomyomectomy is feasible for women with adenomyosis. Surgical outcomes of robotic adenomyomectomy were comparable to those of a laparoscopic approach. There was, however, no superiority of robotic adenomyomectomy in terms of surgical outcomes. Further multicenter prospective studies using standardized surgical procedures are needed to confirm the conclusion of this study.